Coordination-Driven Self-Assembled Metallacycles Incorporating Pyrene: Fluorescence Mutability, Tunability, and Aromatic Amine Sensing - Chang, Xingmao; Zhou, Zhixuan; Shang, Congdi; Wang, Gang; Wang, Zhaolong; Qi, Yanyu; Li, Zhong-Yu; Wang, Heng; Cao, Liping; Li, Xiaopeng; Fang, Yu; Stang, Peter J (Journal of the American Chemical Society, 2019)
Constructing polycyclic aromatics-based, highly emissive fluorophores with good solubility and tunable aggregated structures and properties is of great importance for film fabrication, solution processing, and relevant functionality studies. Herein, we describe a general strategy to endow conventional organic fluorophores with enhanced solubility and modulated fluorescent properties via their incorporation into coordination-driven self-assembled metallacycles. A widely used fluorophore, pyrene, was decorated with two pyridyl groups to yield functionalized pyrene 4. Mixing 4 with three aromatic dicarboxylates with different lengths and a 90° Pt(II) metal acceptor in a 2:2:4 stoichiometric ratio resulted in the formation of three metallacycles, 1, 2, and 3. The metallacycles display good solubility in polar organic solvents, highly aggregation-dependent fluorescence, and size-dependent emissions at higher concentrations. Moreover, metallacycle 2-based, silica-gel-supported film as fabricated not only is more emissive than the ligand 4-based one but also displays much improved sensing properties for amines in the vapor state, as demonstrated by significantly increased response speed and decreased recovery time. The enhanced solubility, unique fluorescence behavior, and multi-factor modulation character show that coordination-driven self-assembly can be utilized for the development of new fluorophores through simple modification of conventional fluorophores. The fluorophores synthesized this way possess not only complex topological structures but also good modularity and tunability in fluorescence behavior, which are important for grafting multi-stage energy-transfer systems necessary for the development of high-performance sensing materials.